Translation Procedures in Translating Religious Terms - Mahatma Agung, I Gusti Ayu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016)
This research aims at investigating the translation procedures applied in translating religious terms. The data was taken from a book entitled ‘The Perfection of Yoga’ written by Prabhup?da and the translated version entitled ‘ Kesempurnaan Yoga ’. The data in this study consists of religious terms in form of words, phrases and expressions. The data was collected by using observation method which was applied at once with the implementation of note-taking technique. The relevant data was analyzed by applying qualitative method since the analysis was conducted in descriptive sentences. The analyzed data was presented by using informal method. Theory of translation procedures proposed by Vinay and Darbelnet (2000) was applied to analyze the translation procedures applied in translating the religious terms. The result of the analysis shows that there are nine translation procedures applied to translate the religious terms. The translation procedures are borrowing, literal translation, transposition, modulation, equivalence, adaptation, amplification, reduction, and explicitation.
Keywords: procedures of translation, religious terms